2017
DOI: 10.1038/s41598-017-13253-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iodinated contrast media on renal perfusion: A randomized comparison study in pigs using quantitative contrast-enhanced ultrasound (CEUS)

Abstract: The administration of iodinated contrast media (CM) can cause microcirculatory disorder leading to acute renal dysfunction. In a prospective, randomized investigation two CM (Iodixanol vs Iopromide) were compared in 16 pigs. Each animal received 10 intra-aortal injections (5 ml Iodixanol or 4.32 ml Iopromide). Microcirculation was assessed using contrast-enhanced ultrasound (CEUS) directly on the kidney surface using time-to-peak (TTP) and blood-volume-analysis. Macroscopic observations were documented. Post m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…This was in line with another animal study in which could be shown that iodinated CM deteriorate the oxygen tension in the renal cortico-medullary region of pigs [18]. The studies [15,17,18] have been conducted within the same animal cohort of the presented study according to the 3R principle (refinement, reduction, and replacement).…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations
“…This was in line with another animal study in which could be shown that iodinated CM deteriorate the oxygen tension in the renal cortico-medullary region of pigs [18]. The studies [15,17,18] have been conducted within the same animal cohort of the presented study according to the 3R principle (refinement, reduction, and replacement).…”
Section: Introductionsupporting
confidence: 84%
“…This had been demonstrated before also in a clinical study [16]. The pig study revealed a transient stasis of the renal microcirculation in different kidney regions, which was more pronounced after administration of Iopromide vs. Iodixanol [17]. This was in line with another animal study in which could be shown that iodinated CM deteriorate the oxygen tension in the renal cortico-medullary region of pigs [18].…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Although hemodynamic assessment by CCDS remains indispensable, CEUS allows a rapid and clear evaluation of arterial and venous organ perfusion of the liver, kidneys, spleen and mesentery. Small areas of reduced microvascularization or early infarctions of the kidneys are not visible in fundamental B-mode, but clearly detectable using dynamic CEUS [8,17].…”
Section: Discussionmentioning
confidence: 98%